Pre-ingestive selection efficiency in two populations of the razor clam Tagelus dombeii with different histories of exposure to paralytic shellfish poisoning (PSP). Issue 4 (3rd July 2016) - Villanueva, Paola A.; Navarro, Jorge M.
Abstract: We studied toxic effects of the dinoflagellate Alexandrium catenella on filtration activity and pre-ingestive selection efficiency in Tagelus dombeii (razor clam). Samples came from two populations with different histories of exposure to paralytic shellfish poisoning (PSP): Melinka, Aysén (with frequent exposure to PSP) and Corral, Valdivia (without previous exposure to PSP). Feeding activity of T. dombeii was affected by a diet containing A. catenella, showing a reduction in individuals from Corral, Valdivia and Melinka, Aysén. Furthermore, pre-ingestive selection efficiency was significantly higher in specimens from the population of Melinka, than those from Corral. Significantly higher values of clearance rate and pre-ingestive selection efficiency from the Melinka samples may reflect adaptation to specific environmental conditions where PSP events frequently occur.